Spheral coherence of society as an imperative of its sustainability and progress - Shavel, Sergei A. (Journal of the Belarusian State University. Sociology, 2019)
Considered is the coherence (cohesion, interpenetration) of the main spheres of society: economy, politics, social sphere, spiritual and cultural life. Two basic sociological paradigms – realism and nominalism – are given analysis to. Three paradigmatic examples (according to T. Parsons) are highlighted: society as part of nature, society as an organism and society as a self-sufficient integrity. Their limitations are revealed. The mechanism of interchange between the main spheres of society according to the scheme «entrance-exit» is described.